REAKSI PASAR MODAL TERHADAP KEMENANGAN IR. H. JOKO WIDODO PADA PEMILIHAN PRESIDEN DI INDONESIA TAHUN 2019 - Resalia Indrianti; Suyanto Suyanto; Sri Retnaning Rahayu (Universitas Muhammadiyah Metro, 2020)
This research is an event study research that aims to find out how big the reaction of the Indonesian capital marketis to the victory of the Joko Widodo pair in the 2019 Presidential Election with the indicators used in the form ofabnormal returns and trading volume activity on the LQ45 index stock group. This study uses secondary data in theform of daily data. stock prices, daily data on LQ45 index, daily data on trading volume, and daily data on thevolume of shares outstanding during the period of seven days before, one day during, and seven days after the event.The day of the event was May 22, 2019. Sampling used a purposive sampling method. The type of data used isquantitative data. The data collection technique in this research is by means of documentation. Testing thehypothesis using the One-Sample t Test and Paired Sample t-Test. The results showed that there were significantdifferences in the reaction between the average before and after the event. However, there is no significantdifference between the average abnormal returns before the event. Similar to the average abnormal return after theevent, there is a significant difference in the average trading volume before and after the event. There is asignificant difference in the average trading volume before and during the event. There is a significant difference inthe average trading volume after and during the event.